The impact of strength training on the prevention of orthopedic injuries in sports: a literature review. - Julia Szewczyk; Michał Świta; Anna Szuciak (Quality in Sport)
Introduction: The perception of physical activity has evolved, influenced by urbanization, media, and public health initiatives. While regular physical activity offers health benefits, musculoskeletal injuries in athletes remain a concern, often going unnoticed due to subtle symptoms. Preventing these injuries is crucial, with strength training (ST) emerging as a strategy to enhance stability and reduce injury risk.